A mesoporous carbon-based catalyst derived from cobalt and boron co-doped melamine formaldehyde gel for oxygen reduction reaction. (10th February 2020) - Cao, Hehuan; Cao, Jidong; Wang, Fanghui; Zhu, Hong; Pu, Min
Abstract: Non-precious metal catalysts are playing an increasingly important role in research on oxygen reduction reaction (ORR) catalysts for fuel cells due to their relatively low cost. In this work, a novel mesoporous catalyst derived from cobalt- and boron-co-doped melamine formaldehyde (MF) gel (Co, B-MF) was successfully synthesized by a facile self-assembly pyrolysis method. It was found that doping of Co and B could provide various active sites and an appropriate pyrolysis temperature was beneficial to increase the number of active sites. As a result, the obtained Co, B-MF-900 catalyst (pyrolyzed at 900 °C) exhibited an outstanding ORR performance in 0.1 M KOH solution with a high onset potential of 1.1 V versus reversible hydrogen electrode (vs RHE), which was 0.1 V higher than that of the commercial Johnson Matthey Pt/C. Additionally, Co, B-MF-900 displayed good stability and superior methanol tolerance. The superior ORR performance of Co, B-MF-900 can be attributed to its mesoporous structure, the synergistic effect of active sites, and the excellent conductivity of the carbon carrier. Graphical abstract: Image 1 Highlights: High activity catalysts were prepared by a facile self-assembly pyrolysis method. The doping of Co and B into melamine-formaldehyde gel made much active sites. Co, B-MF/C-900 showed high activity, great durability, and good methanol tolerance. The ORR catalytic process of Co, B-MF/C-900 was based on a four-electron pathway.